2021
DOI: 10.3389/fonc.2021.608201
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and Pharmacological Evaluation of STEAP4 as a Novel Target for HER2 Overexpressing Breast Cancer

Abstract: Breast cancer (BC) is a highly heterogeneous disease encompassing multiple subtypes with different molecular and histopathological features, disease prognosis, and therapeutic responses. Among these, the Triple Negative BC form (TNBC) is an aggressive subtype with poor prognosis and therapeutic outcome. With respect to HER2 overexpressing BC, although advanced targeted therapies have improved the survival of patients, disease relapse and metastasis remains a challenge for therapeutic efficacy. In this study th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 69 publications
2
10
0
Order By: Relevance
“…Nevertheless, “NMRAL1-Mediated NF-κB Inhibition” might not be the only biological effect of the NADPH oxidoreductase motif of STAMP2. Previous research has also revealed that STAMP2 is involved in tumorigenesis 24 , 25 but functions as a proinflammatory oxidative stress promoter, indicating that it might have an opposite function under different circumstances. More research, including loss-of-function research, needs to be performed in the future for further confirmation.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, “NMRAL1-Mediated NF-κB Inhibition” might not be the only biological effect of the NADPH oxidoreductase motif of STAMP2. Previous research has also revealed that STAMP2 is involved in tumorigenesis 24 , 25 but functions as a proinflammatory oxidative stress promoter, indicating that it might have an opposite function under different circumstances. More research, including loss-of-function research, needs to be performed in the future for further confirmation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicate that STAMP2 performs all of these functions [ 16 , 30 , 41 ]. Furthermore, STAMP2 is associated with metabolic diseases [ 7 , 10 , 25 , 42 ] and is overexpressed in several human cancers [ 32 , 43 , 44 , 45 ], underlining its physiological function in the maintenance of cellular iron homeostasis [ 30 , 42 ].…”
Section: Structure and Function Of Stamp2mentioning
confidence: 99%
“…Orfanou et al found that STEAP4 expression was obvious only in malignant breast tissues, whereas all benign breast cases had no detectable levels. Furthermore, knockdown of STEAP4 also suppressed cell proliferation and enhanced the pharmacological effect of lapatinib (HER2 inhibitor) in HER2-overexpressing breast cancer [ 45 ], confirming its potential oncogenic role in breast cancer. These results in various cancers demonstrate that the growth-inducing and anti-apoptotic roles of STAMP2 are needed for carcinogenesis.…”
Section: Stamp2 In Type 2 Diabetes Inflammatory Diseases and Cancersmentioning
confidence: 99%
“…Jin et al (2015) reported that STEAP4 increases ROS in prostate cancer cells through its iron reductase activity, and subsequently affects proliferation, colony formation, anchorageindependent growth, and apoptosis, involving a mechanism at least partly mediated by activating transcription factor 4 (ATF4). Recently, Orfanou et al (2021) investigated the function of STEAP4 in breast cancer and demonstrated that knockdown of STEAP4 suppresses cell proliferation and enhances the inhibition of lapatinib in HER2-overexpressing breast cancer, predicting an oncogenic role for STEAP4 in breast cancer. On the contrary, STEAP4-mediated increases in intracellular copper levels result in activation of the E3 ligase X-linked inhibitor of apoptosis (XIAP), enhancing IL-17-induced NF-κB activation and inhibiting caspase-3 activity (Liao et al, 2020).…”
Section: Biological Functions and Related Molecular Mechanisms Of Six-transmembrane Epithelial Antigen Of The Prostate In Cancersmentioning
confidence: 99%